ГОСПОДАРСЬКО-ПРАВОВІ ПРОБЛЕМИ ФУНКЦІОНУВАННЯ ДЕРЖАВНИХ ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДІВ - Kutsurubova-Shevchenko, O.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The paper deals with economic and legal problems of state educational establishments functioning. The necessity is grounded to provide economic and legal regulation of social relations in the sphere of higher education.